#TITLE_ALTERNATIVE# - SUSILO (NIM 23304004), JOKO
In present thesis documents the description of simulated and experimental study of tomographic imaging tecnique using ultrasonic to reconstruct the cross-section image in circular object, here it is reinforced concrete. The purpose is to provides procedures and steps how to achieve collected projection data from parallel beam tomography in experimental, examined by 64 measuring point. In this work, collection of parallel projection data is made up from ultrasonic wave velocity, which is obtained by time of flight (ToF) data in through transmission mode along straight line with many different angles. By using the filtered back-projection (FBP) algorithm for parallel tomography, the image can be reconstructed. The objectives of present work were to apply such tecniques for Non-Destructive Test (NDT) of reinforced concrete; determining the posisitions, size and defect as possible matter of steel rods which is tucked vertically inside the concrete and provide answers to the relevant technical issues when building image from simulated and experimental process. Based on the experimental results, it was concluded that the tomographic tecnique is a feasible means for carried out to realize the visually reconstruction, not only composition but also internal condition contained such as circular defect in respect of positions, shape and size exist in an reinforced concrete construction.